Evaluation of a summation formula based on half argument and allied with Recurrence relation (Global Journal of Science Frontier Research, 2012)
The aim of this paper is to evaluate a summation formula based on half argument allied with Hypergeometric function and involving recurrence relation.
Keywords: Contiguous relation; Gauss second summation theorem; Re-currence relation